Intercalibration of ecotoxicity testing protocols with Artemia franciscana. (October 2015) - Manfra, L.; Savorelli, F.; Di Lorenzo, B.; Libralato, G.; Comin, S.; Conti, D.; Floris, B.; Francese, M.; Gallo, M.L.; Gartner, I.; Guida, M.; Leoni, T.; et al.
Highlights: Toxicity tests were carried on Artemia franciscana with copper sulphate pentahydrate & sodium dodecyl sulphate. Acute, long-term & hatching toxicity tests were intercalibrated to evaluate their reliability and reproducibility. The good intercalibration results strongly support standardization and use in the regulatory protocols. Acute hatching test shows more sensitivity than acute mortality test and EC50 values comparable to acute tests with other species. Abstract: The brine shrimp, Artemia spp., is widely used in ecotoxicology as a target biological model. Although several protocols were available in the early 1980s, only the 24-h acute mortality toxicity test was evaluated in a European intercalibration exercise during that period. Nevertheless, documentation of standard methods serving to provide specifications, guidelines or detailed characteristics of the 24-h protocol is still unavailable. This paper present the results of an intercalibration study of three toxicity-testing protocols using Artemia franciscana : (a) the 24-h static acute mortality test, (b) the 48-h static hatching test and (c) the 14-d static-renewal long-term mortality test. A first tier of experiments was conducted by a reference laboratory, which investigated the repeatability of the three methods. The feasibility and reproducibility of these protocols were then investigated by an intercomparison exercise involving 11 participants for the acute mortality test, seven for the acute hatching test and nine for the long-term mortality test. Protocols were tested on reference toxicants (copper sulphate pentahydrate and sodium dodecyl sulphate). The coefficients of variation were <20% and <50% for intra- and interlaboratory activities, respectively. These results encourage the standardization of the proposed methods and their use as regulatory procedures.